Vertically-Ordered Mesoporous Silica Films Grown on Boron Nitride-Graphene Composite Modified Electrodes for Rapid and Sensitive Detection of Carbendazim in Real Samples - Zou, Yanqi; Zhou, Xiaoyu; Xie, Liuhong; Tang, Hongliang; Yan, Fei (Frontiers in Chemistry, 2022)
Carbendazim (CBZ), a kind of widely used pesticide, is harmful to human health and environmental ecology. Therefore, it is of great importance to detect CBZ in real samples. Herein we report the stable growth of vertically-ordered mesoporous silica films (VMSF) on the glassy carbon electrode (GCE) using boron nitride-reduced graphene oxide (BN-rGO) nanocomposite as an adhesive and electroactive layer. Oxygen-containing groups of rGO and 2D planar structure of BN-rGO hybrid favor the stable growth of VMSF via the electrochemically assisted self-assembly (EASA) method. Combining the good electrocatalytic activity of BN-rGO and the enrichment effect of VMSF, the proposed VMSF/BN-rGO/GCE can detect CBZ with high sensitivity (3.70 μA/μM), a wide linear range (5 nM–7 μM) and a low limit of detection (2 nM). Furthermore, due to the inherent anti-fouling and anti-interference capacity of VMSF, direct and rapid electrochemical analyses of CBZ in pond water and grape juice samples are also achieved without the use of complicated sample treatment processes.